The Ottoman Canon and the construction of Arabic and Turkish literatures - Arslan, C. Ceyhun (Edinburgh : Edinburgh University Press, 2024)
No detailed description available for ""The Ottoman Canon and the Construction of Arabic and Turkish Literatures"".
Frontmatter -- Contents -- Acknowledgements -- Note on Translation and Transliteration -- Introduction: Beyond the Influence Paradigm -- 1 A Multilingual Ottoman Ocean: Taverns, Exclusions and Ziya Pasha's Harabat -- 2 Jurjī Zaydān, Literary Comparisons and the Formation of Arabic and Turkish Literatures -- 3 The Ottoman Tarboosh: Disguise and the Novel Genre in Ahmet Midhat's Hasan Mellah and Muḥammad al-Muwayliḥī's What ʻĪsā ibn Hishām Told Us -- 4 Kaʻb ibn Zuhayr Weeps for Sultan Murad IV: Baghdad, Translation and the Turkish Language in Maʻrūf al-Ruṣāfī's Works -- 5 From 'Ottoman Literature is Arabic Literature' to 'Arabs Possess a Literature': Hacı İbrahim, Ahmet Rasim and the Fetters of Influence -- 6 Family Matters: Oedipus, Tawf īq al-Ḥakīm and Ahmet Hamdi Tanpınar -- Conclusion: Modernity, Ottoman Saʻdī and Ottoman al-Mutanabbī -- References -- Index
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed March 6, 2024).
JSTOR
Keywords: Arabic literature -- History and criticism; Turkish literature -- History and criticism; Littérature arabe -- Histoire et critique; Littérature turque -- Histoire et critique; HISTORY / Middle East / Turkey & Ottoman Empire